Value Co-Creation through Service Interaction Quality: Evidence from Engagement, Communication, and Revisit Intention in Mandalika SEZ - Islam, Egista Syiarul; Dakwah, Muhammad Mujahid (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates how customer engagement and marketing communication influence revisit intention through the mediating role of service interaction quality in the Mandalika Special Economic Zone (SEZ), Indonesia. The research aims to explain how customer engagement and marketing communication are translated into revisit intention through high-quality, reciprocal, and trust-based service interactions. Theoretically, this study contributes to the extension of the Service-Dominant Logic by identifying service interaction quality as an operant resource that enables value co-creation between tourists and service providers. Practically, the findings offer insights for destination managers and policymakers to strengthen interaction-driven strategies that foster repeat visitation and sustainable tourism competitiveness. Data were collected from 204 tourists who had visited Mandalika within the past 12 months using purposive sampling and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that customer engagement and marketing communication significantly enhance service interaction quality. However, only marketing communication exerts a direct effect on revisit intention, while customer engagement influences it indirectly through interaction quality. These findings highlight that engagement and communication must be supported by high-quality service interactions to generate destination loyalty, emphasizing the importance of culturally adaptive and community-based exchanges in emerging tourism destinations.